2022
DOI: 10.1177/17531934221102251
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after extension block pinning for fracture-dislocations of the proximal interphalangeal joint

Abstract: The long-term outcomes of extension block pinning used to treat unstable dorsal fracture-dislocations of the proximal interphalangeal joint have been investigated in a single centre. Thirty-one patients (33 fingers) had a clinical and radiological assessment at a mean follow-up of 16 years. Excluding one joint salvaged with an arthrodesis, the mean active range of motion of the joints was 80° with a mean 5° extension deficit. The mean active range of motion of the distal interphalangeal joint was 64°. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…There is risk of injury to the central band and stiffness is often a consequence of the limited arc of motion. Nordback et al (2022) reported satisfactory clinical outcomes for extension block pinning with a mean arc of 80 in 33 cases at a mean follow-up of 16 years. They noted that 47% of patients had pain during activity, which could be related to arthritic changes.…”
Section: Proximal Interphalangeal Joint Fracture-dislocationsmentioning
confidence: 94%
“…There is risk of injury to the central band and stiffness is often a consequence of the limited arc of motion. Nordback et al (2022) reported satisfactory clinical outcomes for extension block pinning with a mean arc of 80 in 33 cases at a mean follow-up of 16 years. They noted that 47% of patients had pain during activity, which could be related to arthritic changes.…”
Section: Proximal Interphalangeal Joint Fracture-dislocationsmentioning
confidence: 94%
“…Because of the high failure rate of conservative treatment, more and more surgeons are advocating early surgical intervention after injury. The most classic form of the procedure is the Ishiguro's method, which has been reported to be effective, but there are still some shortcomings, such as stiffness of joints and cartilage damage ( 1 , 2 ). So we modified the design of the method.…”
Section: Introductionmentioning
confidence: 99%